Desain dan Implementasi Sistem Monitoring Jaringan Menggunakan Zabbix dan Telegram - Malik, Prasetyo Fajar; Josaphat, Bony Parulian (Politeknik Statistika STIS, 2024)
The BPS Data Center requires an integrated monitoring system to ensure the integrity and accessibility of statistical data. Currently, the system is fragmented by device type and brand, lacking the ability to send real-time alerts to mobile devices. This research focuses on designing and implementing a monitoring system at the BPS Data Center. Furthermore, this research endeavors to forward alert from the monitoring system into mobile notifications. The study employs the Network Development Life Cycle (NDLC) methodology. From the results of the analysis using Pugh matrix, it was obtained that Zabbix was the selected monitoring application service and Telegram as the mobile application that utilizes the Bot feature to send notifications using webhook method. Based on the evaluation results from Black-box testing and SUS, it was found that overall, the system features were successfully tested with expected outputs, and the system interface received an “acceptable” rating from users.